2009
DOI: 10.1016/j.bbr.2008.08.036
|View full text |Cite
|
Sign up to set email alerts
|

The underestimated role of olfaction in avian reproduction?

Abstract: Until the second half of the 20 th century, it was broadly accepted that most birds are microsmatic if not anosmic and unable to detect and use olfactory information. Exceptions were eventually conceded for species like procellariiforms, vultures or kiwis that detect their food at least in part based on olfactory signals. During the past 20-30 years, many publications have appeared indicating that this view is definitely erroneous. We briefly review here anatomical, electrophysiological and behavioral data dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 105 publications
(133 reference statements)
2
87
0
3
Order By: Relevance
“…In mammals and fish, peptides derived from MHC proteins can contribute to individual olfactory profiles that subsequently play a role in mate choice decisions [8,77,78]. Birds appear also to have sophisticated olfactory capabilities [79], and there has been an explosion of studies from a wide range of avian orders showing a link between olfaction and mate choice [80 -82] or other behaviours [83 -85]. Although nothing is known of frigatebird olfaction, female great frigatebirds reject males at both stages of mate choice-at the initial stage of flying over displaying males and also at the subsequent stage of perching in physical contact (Dearborn & Juola 2005, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and fish, peptides derived from MHC proteins can contribute to individual olfactory profiles that subsequently play a role in mate choice decisions [8,77,78]. Birds appear also to have sophisticated olfactory capabilities [79], and there has been an explosion of studies from a wide range of avian orders showing a link between olfaction and mate choice [80 -82] or other behaviours [83 -85]. Although nothing is known of frigatebird olfaction, female great frigatebirds reject males at both stages of mate choice-at the initial stage of flying over displaying males and also at the subsequent stage of perching in physical contact (Dearborn & Juola 2005, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it has been shown that olfaction may be a more important sense in birds than was traditionally believed (Steiger et al 2008). Recent evidence suggests that birds can use odours in several ecological contexts and with different functions (Roper 1999, Hagelin 2007, Hagelin & Jones 2007, Rajchard 2007, 2008, Balthazart & Taziaux 2009, Caro & Balthazart 2010. At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010).…”
mentioning
confidence: 99%
“…Mammals are well known for using olfactory social communication whereas birds are traditionally considered to be microsmatic and to rely on sight and sound rather than olfaction (reviewed by Balthazart and Taziaux, 2009;Hagelin and Jones, 2007;Jones and Roper, 1997). However, a growing body of evidence suggests that olfaction may play an important and hitherto underestimated role for birds in different contexts (Balthazart and Taziaux, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that olfaction may play an important and hitherto underestimated role for birds in different contexts (Balthazart and Taziaux, 2009). A series of studies has shown that seabirds strongly rely on their sense of smell.…”
Section: Introductionmentioning
confidence: 99%